2016
DOI: 10.1038/srep35546
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile hormone regulation of female reproduction in the common bed bug, Cimex lectularius

Abstract: To begin studies on reproduction in common bed bug, Cimex lectularius, we identified three genes coding for vitellogenin (Vg, a protein required for the reproductive success of insects) and studied their hormonal regulation. RNA interference studied showed that expression of Vg3 gene in the adult females is a prerequisite for successful completion of embryogenesis in the eggs laid by them. Juvenile hormone (JH) receptor, Methoprene-tolerant (Met), steroid receptor coactivator (SRC) and GATAa but not ecdysone r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 41 publications
3
50
0
Order By: Relevance
“…The expression of Vg, the major yolk protein in oocyte, is regulated by JH via its receptor Met, which has been documented in A. aegypti ( Raikhel et al, 2005 ; Zou et al, 2013 ), P. apterus ( Smykal et al, 2014 ), and T. castaneum ( Parthasarathy et al, 2010 ). Other studies in Cimex lectularius ( Gujar and Palli, 2016 ) and Nilaparvata lugens ( Lin et al, 2015 ) also confirmed that Met was required for Vg expression and ovarian development. Our RNAi experiment revealed that knockdown of HaMet resulted in the significant decline of Vg expression in the fat body, the reduced expression of VgR in the ovary, and the atrophied ovaries with less yolk protein deposition.…”
Section: Discussionmentioning
confidence: 62%
“…The expression of Vg, the major yolk protein in oocyte, is regulated by JH via its receptor Met, which has been documented in A. aegypti ( Raikhel et al, 2005 ; Zou et al, 2013 ), P. apterus ( Smykal et al, 2014 ), and T. castaneum ( Parthasarathy et al, 2010 ). Other studies in Cimex lectularius ( Gujar and Palli, 2016 ) and Nilaparvata lugens ( Lin et al, 2015 ) also confirmed that Met was required for Vg expression and ovarian development. Our RNAi experiment revealed that knockdown of HaMet resulted in the significant decline of Vg expression in the fat body, the reduced expression of VgR in the ovary, and the atrophied ovaries with less yolk protein deposition.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, in our study the fecundity of Krā€h1 ā€depleted adults was reduced. Interestingly, knockdown of Krā€h1 in female adults of Cimex lectularius did not reduce their fecundity but affected the development of their embryos (Gujar & Palli, ). Taken together, these studies demonstrate that there are some differences amongst insect species in the mechanisms by which the JH signalling pathway regulates vitellogenesis and ovarian development.…”
Section: Discussionmentioning
confidence: 99%
“…In the mosquito Aedes aegypti, Kr-h1 can activate and repress the expression of its target genes for previtellogenic development and egg production in response to JH (Ojani et al, 2018;Shin et al, 2012;Zou et al, 2013). Depletion of Kr-h1 in adult females of the common bed bug Cimex lectularius does not reduce the egg number but severely reduces the egg hatchability (Gujar and Palli, 2016). In the migratory locust Locusta migratoria, Kr-h1 mediates JH action to promote vitellogenesis, ovarian development and oocyte maturation (Song et al, 2014).…”
Section: Introductionmentioning
confidence: 99%